2011
DOI: 10.5402/2011/237501
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Fluconazole -Cyclodextrin Complex Ocuserts: In Vitro and In Vivo Evaluation

Abstract: The main purpose of the present study was to develop ocuserts of Fluconazole β-CD (beta-cyclodextrin) complex and to evaluate both in vitro and in vivo. Fluconazole was made complex with β-CD, and the release rate was controlled by HPMC K4M and ethyl cellulose polymers using dibutyl Phthalate as permeability enhancer. Drug-polymer interactions were studied by Fourier transform infrared spectroscopic studies. The formulated ocuserts were tested for physicochemical parameters of in vitro release and in vivo perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The formed dispersion was cast for 24 h at 25 ± 1 °C in a Petri dish with a diameter of 12 cm. A glass funnel was inverted and placed on top of the Petri dish to control the rate and pattern of solvent evaporation ( Abdul Ahad et al, 2011 ). After complete drying, the films were cut into uniformly sized circles (10 mm in diameter) using a borer made from stainless steel.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The formed dispersion was cast for 24 h at 25 ± 1 °C in a Petri dish with a diameter of 12 cm. A glass funnel was inverted and placed on top of the Petri dish to control the rate and pattern of solvent evaporation ( Abdul Ahad et al, 2011 ). After complete drying, the films were cut into uniformly sized circles (10 mm in diameter) using a borer made from stainless steel.…”
Section: Methodsmentioning
confidence: 99%
“…The inserted OCUs were carefully removed at 1 h (group 1), 2 h (group 2), 4 h (group 3), 8 h (group 4), 12 h (group 5), 16 h (group 6), 20 h (group 7) and 24 h (group 8), and analyzed spectrophotometrically for drug content as mentioned in the drug loading section at λ max of 212 nm. The remaining VLD amount in the tested removed ocusert was subtracted from the initial drug content of VSO-0 to obtain the amount of VLD released in the rabbit eye ( Abdul Ahad et al, 2011 ). After each experiment, the animals used were sent to the animal house for disposal according to its rules.…”
Section: Methodsmentioning
confidence: 99%
“…It is considered the first line to treat a wide range of superficial and systematic fungal infections with Candida species [ 33 ] due to the lower side effects [ 34 ] and the reported low toxicity [ 30 ]. It is also prescribed for patients suffering from acquired immunodeficiency syndrome (AIDS) [ 35 ] and patients subjected to immunosuppressant therapies such as cancer and transplant patients acute leukemia [ 36 ], and bone marrow transplantation patients [ 37 ] to prevent cryptococcal meningitis, the non- albicans candidiasis , and yeast infections, respectively [ 34 , 38 , 39 , 40 , 41 ]. FZ’s mechanism of action inhibits producing the major fungal cell membrane lipid ergosterol [ 34 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the low aqueous solubility of the drug could affect its bioavailability and therapeutic performance [ 34 ]. Different research groups reported many complexation studies of the FZ with varying types of naturally occurring and semisynthetic macrocyclic cyclodextrins [ 38 , 48 , 55 , 56 , 57 , 58 ]. Abranches et al [ 34 ] reported a complexation study of FZ with sodium p -sulfonatocalix[ n ]arenes ( n = 4 and 6).…”
Section: Introductionmentioning
confidence: 99%
“…Ocuserts containing fluconazole β-cyclodextrin complex has been evaluated to treat eye infections and found that the drug delivery system retained the drug concentration at the intended site of action for sufficient period of time and elicited desired pharmacological activity. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%